Single layer PbI2: hydrogenation-driven reconstructions. Issue 92 (20th September 2016) - Bacaksiz, C.; Sahin, H.
Abstract : By performing density functional theory-based calculations, we investigate how a hydrogen atom interacts with the surfaces of monolayer PbI2 and how one- and two-side hydrogenation modifies its structural, electronic, and magnetic properties. Abstract : By performing density functional theory-based calculations, we investigate how a hydrogen atom interacts with the surfaces of monolayer PbI2 and how one- and two-side hydrogenation modifies its structural, electronic, and magnetic properties. Firstly, it was shown that the T-phase of single layer PbI2 is energetically more favorable than the H-phase. It is found that hydrogenation of its surfaces is possible through the adsorption of hydrogen on the iodine sites. While H atoms do not form a particular bonding-type at low concentration, by increasing the number of hydrogenated I-sites well-ordered hydrogen patterns are formed on the PbI2 matrix. In addition, we found that for one-side hydrogenation, the structure forms a (2 × 1) Jahn–Teller type distorted structure and the bandgap is dramatically reduced compared to hydrogen-free single layer PbI2 . Moreover, in the case of full hydrogenation, the structure also possesses another (2 × 2) reconstruction with a reduction in the bandgap. The easily tunable electronic and structural properties of single layer PbI2 controlled by hydrogenation reveal its potential uses in nanoscale semiconducting device applications.